A new species of the genus Nycterotis Felder, 1874 from Central Brazil (Lepidoptera: Notodontidae, Nystaleinae) - V. O. Becker (SHILAP, 2018)
Nycterotis rhudarioides Becker, sp. n., belonging to the aroata-group, from Central Brazil, is described.